On the significance of geographical proximity for the structure and development of newly founded knowledge-intensive business service firms - Thomas Stahlecker; Knut Koschatzky (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2004)
A key feature of the knowledge-based economy is a remarkable increase in the number, foundation rates, and employees of knowledge-intensive business service firms (KIBS). KIBS are knowledge-intensive, in the sense that they are founded upon highly specialised knowledge. Based on the assumption that knowledge and knowledge organisation are tied to personal capabilities and information, spatial proximity to knowledge-providers and -users appears to be crucial in the development and growth process of KIBS. The idea that the region affects foundation activities primarily derives from a resource-based view. Different regional environments (e.g. configurations of incubator and intermediate organisations, regional entrepreneurial social infrastructure) and the foundation pattern of KIBS are obviously interrelated. In addition to environmental factors affecting the development or growth of newly founded KIBS, factors related to the entrepreneur of KIBS and to characteristics of the KIBS firms have to be taken into consideration. Based upon a survey with founders of KIBS firms in three German regions, a selection of indicators will be used as determinants for new KIBS growth. Comparing the successful KIBS start-ups with those showing an employment decrease in the relevant time period, it has to be emphasized that KIBS with employment increase co-operate with other firms and institutions on all spatial levels, regardless of the function of the partner firms for the KIBS activities.
urn:nbn:de:0011-n-286081
Keywords: 330; KIBS; Region; Spatial proximity; Growth; Unternehmensgründung; Unternehmensdienstleistung; Wissen; Regionale Konzentration; Deutschland